Finlandiya joins NATO: Patterns of evaluation in Turkish media registers - Erten-Johansson, Selcen (Finland, 2026)
Following Russia’s invasion of Ukraine, Finland reconsidered its longstanding policy of military non-alignment, ultimately deciding to apply for NATO membership. As a NATO member since 1952, Türkiye played a key role in this process, which sparked extensive discussion in Turkish media. This study investigates how Finland and its NATO accession are evaluated across two Turkish media registers – Sözcü news reports and Ekşi Sözlük interactive discussions – through a corpus-based approach grounded in register theory. The research explores how the situational characteristics of each register shape the expression of evaluative language, both overt and covert. Employing keyword and concordance analyses combined with qualitative interpretation, the study examines evaluative and non-evaluative uses of language, with particular focus on the term country and its surrounding context on a positive-negative axis. The findings reveal that news reports tend to express evaluation subtly, often embedding it in covert forms that align with societal norms and values. In contrast, interactive discussions rely on more direct and explicit evaluative language. The analysis highlights how patterns of evaluation are shaped by the communicative functions of each register. Portrayals of Finland also diverge: news media frame Finland’s foreign policy in a largely positive light while expressing criticism of its domestic leadership, whereas online discussions emphasize Finland’s military strength and quality of life, yet raise scepticism about its NATO membership. Overall, this study illustrates how differing media registers contribute to distinct constructions of a country’s portrayal.
Keywords: Turkish media registers, Finland’s NATO accession, keyword analysis, concordance analysis, evaluation patterns, media representation.